A qualitative investigation into pregnancy experiences and maternal healthcare utilisation among adolescent mothers in Nigeria - Christiana A. Alex-Ojei; Clifford O. Odimegwu; Lorretta F. C. Ntoimo (BMC, 2023)
Abstract Background Adolescent maternal healthcare utilisation is low in Nigeria, and little is understood about the pregnancy experiences and drivers of maternal healthcare utilisation among of adolescent girls. This study investigated the pregnancy experiences and maternal healthcare utilisation among adolescent mothers across Nigeria. Methods The study used the qualitative design. Urban and rural communities in Ondo, Imo and Katsina states were selected as research sites. Fifty-five in-depth interviews were conducted with adolescent girls who were currently pregnant or had given birth to a child recently, and nineteen in-depth interviews were conducted with older women who were either mothers or guardians of adolescent mothers. Additionally, key informant interviews were conducted with five female community leaders and six senior health workers. The interviews were transcribed, and resulting textual data were analysed via framework thematic analysis using a semantic and deductive approach, with the aid of NVivo software. Results The findings showed that the majority of unmarried participants had unintended pregnancies and stigma against pregnant adolescents was common. Social and financial support from family members, maternal support and influence, as well as healthcare preferences shaped by cultural and religious norms were the major drivers of maternal healthcare use among adolescent mothers, and the choice of their healthcare providers. Conclusions Interventions to support adolescent mothers and increase maternal healthcare utilisation among them must focus on ensuring the provision of social and financial support for adolescent mothers, and should be culturally sensitive.